2007
DOI: 10.1111/j.1365-2664.2007.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and landscape effects on cross‐pollination rates observed at long distance among French oilseed rape Brassica napus commercial fields

Abstract: Summary 1.Evaluation of our ability to predict cross-pollination rates (CPR) at long distance using dispersal functions estimated in experimental set-ups differing by either their scale or their environmental conditions is crucial to establish appropriate management rules following the release of genetically modified (GM) crops. 2. From 1998 to 2004 we measured oilseed rape CPR in commercial fields for 44 donor-recipient couples separated by 220 up to 2000 m, from up to three different pollen donor cultivars i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…Since feral plants derived from cultivation (as distinct from import) occur at too low a frequency to affect the tolerance threshold of 0.9% in the EU, even if they were assumed all to be transgenic, several authors concluded that feral GMHT plants resulting from seed import spills will have little relevance as a potential source of pollen or seed for GM admixture in conventional oilseed rape crops (Messéan et al, 2009;Squire et al, 2011;Devos et al, 2012 (Colbach et al, 2001a(Colbach et al, ,b, 2005Devaux et al, 2005Devaux et al, , 2007Devaux et al, , 2008Gruber and Claupein, 2006;Knispel et al, 2008;Colbach, 2009)" (EFSA, 2009b.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since feral plants derived from cultivation (as distinct from import) occur at too low a frequency to affect the tolerance threshold of 0.9% in the EU, even if they were assumed all to be transgenic, several authors concluded that feral GMHT plants resulting from seed import spills will have little relevance as a potential source of pollen or seed for GM admixture in conventional oilseed rape crops (Messéan et al, 2009;Squire et al, 2011;Devos et al, 2012 (Colbach et al, 2001a(Colbach et al, ,b, 2005Devaux et al, 2005Devaux et al, , 2007Devaux et al, , 2008Gruber and Claupein, 2006;Knispel et al, 2008;Colbach, 2009)" (EFSA, 2009b.…”
Section: Resultsmentioning
confidence: 99%
“…Using male-sterile plants (which produce no pollen of their own) as recipients tends to overestimate the actual frequency of cross-fertilisation that would occur between the crop plants and pollen-fertile ferals by more than 10-fold (Ramsay et al, 2003; GR Squire, unpublished data), but demonstrates the potential for its occurrence. This approach combined with modelling work confirmed that cross-fertilisation levels usually decline very steeply with distance from one field to an adjacent or nearby field Beckie and Hall, 2008), but they occur at low frequency over several kilometres (Rieger et al, 2002;Ramsay et al, 2003;Devaux et al, 2005Devaux et al, , 2007Devaux et al, , 2008Chifflet et al, 2011). It is expected that crossing of the order of 1 to 10% will occur to feral plants a few metres from a donor, and of 0.1 to 0.01% to ferals that are 100 m away (SIGMEA, 2010).…”
Section: Concern Raised By Austriamentioning
confidence: 97%
See 1 more Smart Citation
“…Few direct measurements to quantify crossings between commercially grown oilseed rape and feral plants have been made so far, but the fact that crossing occurs, and hence genomes of old and new varieties combine, was demonstrated at several localities in the EU (Charters et al, 1999;Bond et al, 2004;Dietz-Pfeilstetter et al, 2006Pascher et al, 2006Pascher et al, , 2010Elling et al, 2009). More generally, the potential for cross-fertilisation of feral plants by the crop plant simultaneously in flower over a range of distances has been demonstrated by the use of small groups of male-sterile recipient plants distributed in the landscape (Ramsay et al, 2003;Devaux et al, 2005Devaux et al, , 2007Devaux et al, , 2008Chifflet et al, 2011). Using male-sterile plants (which produce no pollen of their own) as recipients tends to overestimate the actual frequency of cross-fertilisation that would occur between the crop plants and pollen-fertile ferals by more than 10-fold (Ramsay et al, 2003;GR Squire, unpublished data), but demonstrates the potential for its occurrence.…”
Section: Concern Raised By Austriamentioning
confidence: 99%
“…During the last two decades a number of studies were devoted to the assessment and modeling of pollen flow in different crops in order to evaluate the possibility for coexistence between transgenic and nontransgenic plants (sunflower (1); trees (6); maize (3); oilseed rape (4,5,23).…”
Section: Introductionmentioning
confidence: 99%